PSYCHOLOGICAL ASPECTS OF THE FORMATION OF MORAL SELF-AWARENESS OF ADOLESCENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Psychological aspects of the formation of a teenager's moral self-awareness in the article will be discussed. In particular, based on the generalized ideas of modern scientists, it is emphasized that the formation of moral self-awareness is stablely connected with the peculiarities of the educational environment of adolescents, its moral competence, the peculiarities of the development of moral feelings, and the position of a person of this age category in the reference environment.